Socioeconomic dynamics of multiple mobile phone (M2P) usage and communication in Ota, Nigeria (2012)
Multiple mobile phone (M2P) usage has become an increasing practice in Nigeria but little is known about the factors propelling it or related communication processes. An examination of its operations reveals interaction with economic and social factors for reduction in call costs and management of network fluctuation, limitation and failure. While M2P users are active and goal-oriented, usage behaviour is associated with socioeconomic variables, including electronic finance and marketing. Findings indicate that technological advancement has not created imbecility but consumers with the freewill of determining their communication needs and choices. The study is unique in examining this phenomenon and its implications for developing economies.